Frequency of Hypertension in Patients with Intracranial Hemorrhage Presenting to Emergency Department: Hypertension in Patients with Intracranial Hemorrhage - Malik, Hoorish; Abdullah, Sadaf (Pakistan Journal of Health Sciences, 2025)
Intracranial haemorrhage is a serious neurological emergency with high morbidity and mortality. Hypertension is a known major risk factor; however, local data regarding its frequency in intracranial haemorrhage patients remain limited. Objectives: To determine the frequency of hypertension among patients with intracranial haemorrhage presenting to the Emergency Department (ED) of Lady Reading Hospital, Peshawar. Methods: This cross-sectional study was conducted at the ED of Lady Reading Hospital from April to September 2023. A total of 182 patients aged 30–70 years, diagnosed with intracranial haemorrhage via CT scan, were enrolled using consecutive sampling. Blood pressure, BMI, demographic data, and socioeconomic status were recorded. Hypertension was defined as SBP ≥140 mmHg, DBP ≥90 mmHg, or self-reported antihypertensive medication use. Data were analyzed using SPSS version 26.0, with the chi-square test (p<0.05 considered significant). Results: Patients had a mean age of 50.24 ± 12.24 years and a mean BMI of 25.74 ± 4.41 kg/m². Hypertension was found in 155 patients (85.2%). There were no significant associations between hypertension and gender (p=0.364), age groups (p=0.817), or socioeconomic status (p=0.613). Conclusions: Hypertension prevalence was high among intracranial haemorrhage patients. This emphasizes the need for improved hypertension management and preventive strategies in the community.